2020
DOI: 10.1080/1828051x.2020.1819896
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of sodium selenite, selenised yeast and nanosized elemental selenium on performance response, immunity and antioxidative function of broiler chickens

Abstract: Although selenium (Se) supplementation is a common practice in poultry, the best source and level has not been established yet. Thus, a 42-day experiment involving diets with three levels (0.1, 0.2 and 0.5 mg/kg) of supplemental Se from sodium selenite (SS), selenised yeast (SY) and nanoelemental Se (SN) was conducted to evaluate the possible differential responses of broiler chickens to inorganic, organic and nano Se sources relative to a control diet. Throughout the experiment, broilers receiving Se suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…These results confirm the researches in broiler chickens that found the positive effects of SS in increasing feed intake and body weight (Attia et al., 2010 ; Jakhar et al., 2001 ) and improving the protein‐synthesizing ability of the body (Sun et al., 2016 ). Our results also agree with the findings of other researchers who observed no difference between the effects of SeNPs and SS on broiler chicken performance (Boostani et al., 2015 ; Wang, 2009 ), although there are also findings on better effects of SeNPs on growth and feed conversion efficiency in broiler chickens and quails (Divya et al., 2019 ; Pardechi et al., 2020 ). However, these results are not directly comparable due to differences in treatment patterns.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirm the researches in broiler chickens that found the positive effects of SS in increasing feed intake and body weight (Attia et al., 2010 ; Jakhar et al., 2001 ) and improving the protein‐synthesizing ability of the body (Sun et al., 2016 ). Our results also agree with the findings of other researchers who observed no difference between the effects of SeNPs and SS on broiler chicken performance (Boostani et al., 2015 ; Wang, 2009 ), although there are also findings on better effects of SeNPs on growth and feed conversion efficiency in broiler chickens and quails (Divya et al., 2019 ; Pardechi et al., 2020 ). However, these results are not directly comparable due to differences in treatment patterns.…”
Section: Discussionsupporting
confidence: 93%
“…Talebi et al (2017) also showed that the use of 0.3 mg/kg of Se as SeNPs was more efficient in comparison with the same amount of organic Se in inhibiting the destructive effects of AFB 1 on antibody titers against NDV and SRBC. Pardechi et al (2020) showed that enhancing the antibody response against SRBC requires higher Se than AIV and the use of more available sources such as SeNPs is more suitable to achieve this goal. However, in their study, Se supplementation did not affect the NDV titer.…”
Section: 3%mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we proved a positive effect of SeNPs on the antioxidant status of rats [16][17][18] and ejaculate quality of boars [19][20][21]. The conclusive effect of SeNPs has been proven by similar studies [22][23][24][25].…”
Section: Discussionmentioning
confidence: 81%
“…Analysis of available literature sources shows that there are too few published data on the optimal rates of selenium introduction in compound feed for ducklings raised for meat and they are contradictory. However, it is well known that the minimum selenium requirement for all poultry species is 0.10 mg/kg of feed (Pardechi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%